1974
DOI: 10.1017/s0016672300014786
|View full text |Cite
|
Sign up to set email alerts
|

An extensive behavioural and genetic analysis of the Pawn mutants inParamecium aurelia

Abstract: Pawns are behavioural mutants which show impairment in membrane excitability and are, therefore, devoid of normal avoiding reactions. We obtained 103 lines of Pawns through mutagenesis and screening. Among those that yielded to breeding studies, 59 lines belonged to the pwA complementation group and 38 lines belonged to the pwB group. No other genie loci were found in this extensive analysis. Mutants of the pwA locus showed various degrees of phenotypic leakiness. Based on the pheno-and genotypic differences, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

1974
1974
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…2). Pawn A, a slightly leaky mutant (Chang et al, 1974), showed barely significant avoidance at 41 or 42 "C, and none at all at lower temperatures, and Pawn B (non-leaky) showed no avoidance at any temperature tested. Values of IM were the same for both Pawn mutants, and were essentially unaltered by the test temperature (data not shown).…”
Section: Behaviour Of Pawn Mutantsmentioning
confidence: 90%
“…2). Pawn A, a slightly leaky mutant (Chang et al, 1974), showed barely significant avoidance at 41 or 42 "C, and none at all at lower temperatures, and Pawn B (non-leaky) showed no avoidance at any temperature tested. Values of IM were the same for both Pawn mutants, and were essentially unaltered by the test temperature (data not shown).…”
Section: Behaviour Of Pawn Mutantsmentioning
confidence: 90%
“…We used the "heat-sensitive pawns", pawn C (stock d4-131, genotype pwC/pwC) and pawn A 1 (stock d4-132, genotype pwA1/pwA1) and wild type (stock 51 s) from which the mutants were derived. The double mutant r7 (genotype pwA1/pwA1 pwC/pwC) was an autogamous F2 line derived from a cross between d4-131 and d4-132 and was genotypically verified by a backcross (Chang & Kung, 1973b).…”
Section: Stocks and Culturementioning
confidence: 99%
“…A double mutant bred to contain both mutations, pwA1 and pwC and fails to generate avoiding reactions when grown at 23 ~ (Chang & Kung, 1973b;Satow, Chang & Kung, 1974). The evoked response was recorded from the pwA/pwC double mutant.…”
Section: The Double Mutantmentioning
confidence: 99%
See 2 more Smart Citations